The Influence of Prilension Stickers (Principles of Balanced and Safe Nutrition) on Students' Ability to Identify School Children's Snacks - Erowati, Dewi; Yolahumaroh, Yolahumaroh; Marlina, Yessi (Poltekkes Kemenkes Riau, 2025)
Introduction : Providing nutritional education about healthy foods during childhood not only prevents several causes of major disease and death, but can also reduce health costs and improve the quality of human life. Therefore, elementary school children need to receive education regarding school children's snacks. Researchers have developed nutrition education media in the form of Prilension Stickers (Principles of Balanced and Safe Nutrition) which contain short messages regarding the grouping of healthy snacks according to the principles of balanced nutrition. The objectives of the research is analyze the effect of education on students' ability to identify school children's snacks with the principles of balanced and safe nutrition. Method : This research method is a quasi-experimental pre-post test which analyzes students' ability to identify school children's snacks before and after being given education using Prilension Stickers. The research data consisted of 61 respondents who were students at SDN 2 Pekanbaru City, with a sampling technique using simple random sampling. The data analysis uses SPSS, The Wilcoxon Signed Rank test to evaluate paired samples (scores before and after education). Results : The test Wilcoxon signed rank results show that there is an effect of nutrition education on school children's snacks with Prilension Stickers on students' ability to identify school children's snacks with the principles of balanced and safe nutrition (Sig. < 0.005). Conclusion : It is important to provide nutritional education to increase knowledge in order to change school children's snacking habits and improve children's nutritional status.